The Relationship Between the Level Of Knowledge and Attitude with the Practice Of Implementing Occupational Safety and Health (K3) among Mechanical Engineering Students - dika angga setyawan; Rezania Asyfiradayati (JURNAL KESMAS DAN GIZI (JKG), 2026)
Occupational Safety and Health (OSH) education is essential in vocational schools, as practical activities carry a potential risk of workplace accidents. A health promotion approach emphasizes improving knowledge, fostering positive attitudes, and establishing safe behavior through education, strengthening safety culture, and creating a supportive learning environment from the early stages of education. Health promotion efforts in schools are expected to develop sustainable occupational safety behavior among students. This study aims to analyze the relationship between knowledge and attitudes with the practice of OSH implementation among Mechanical Engineering students at SMK N 1 Sawit Boyolali. This research is a quantitative study with an analytical approach using a cross-sectional design. Data were collected through questionnaires measuring knowledge, attitudes, and OSH practices. Data analysis was conducted using the Spearman correlation test. The results showed that most students had a high level of OSH knowledge (70.0%) and positive attitudes toward OSH (67.2%). Knowledge was not significantly related to OSH practice (r = 0.139; p = 0.064), indicating a very weak correlation. In contrast, attitudes had a significant but very weak relationship with OSH practice. These findings indicate that good knowledge does not necessarily translate into consistent safety behavior, while positive attitudes tend to support safer practices, although they are influenced by other factors such as the practice environment, supervision, and availability of safety facilities. In conclusion, strengthening practical OSH learning based on health promotion, improving supervision, and providing supportive school environments are necessary to enhance the consistency of OSH implementation among students. Further research is needed to examine other factors influencing occupational safety behavior.